Evaluación de la sustentabilidad de cinco unidades productivas de CACAO (Theobroma cacao L.) en el cantón Quevedo de la provincia de los Ríos - Avilés Bravo, Armando Enrique (2022)
Sustainability in the cocoa farms in the Quevedo area is something that today suffers from an imbalance due in large part to ignorance of the techniques used or based on traditional techniques that date back about 60 years. The present investigation was carried out with the objective of evaluating the sustainability of five conventional agricultural systems of cocoa cultivation in the Quevedo canton in the Province of Los Ríos.